2019
DOI: 10.1111/bdi.12872
|View full text |Cite
|
Sign up to set email alerts
|

Number of episodes in bipolar disorder: The case for more thoughtful conceptualization and measurement

Abstract: Objectives Number of mood episodes (NoE) may be an important prognostic indicator in bipolar disorder, with implications for treatment. However, NoE has been conceptualized and measured inconsistently throughout the literature. This review examines the construct of NoE in bipolar disorder, with the aim of enhancing its conceptualization and measurement. Methods A critical evaluation of literatures on important correlates of NoE, conceptually and phenomenologically overlapping features, and previous studies con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 105 publications
(142 reference statements)
0
22
0
Order By: Relevance
“…There is evidence that risk of recurrence increases with the number of prior episodes of bipolar disorder and a greater number of episodes is also associated with more chronic symptoms, and functional impairment (Tremain et al, 2020b). Number of episodes may also moderate the response to treatments, particularly adjunctive psychosocial treatments.…”
Section: Management Of Bipolar Disordermentioning
confidence: 99%
“…There is evidence that risk of recurrence increases with the number of prior episodes of bipolar disorder and a greater number of episodes is also associated with more chronic symptoms, and functional impairment (Tremain et al, 2020b). Number of episodes may also moderate the response to treatments, particularly adjunctive psychosocial treatments.…”
Section: Management Of Bipolar Disordermentioning
confidence: 99%
“…Increasing the understanding of the experiences of those within later stage is a step toward precision psychiatry. A benefit of this approach to adding granularity to staging over reliance on clinical history is avoiding validity and reliability concerns resulting from the recall and measurement‐related issues assessment of distal and often distressing events inherently involves 41 . Indeed, data about current symptoms, functioning, quality of life, and medication effectiveness are routinely collected as part of clinical assessment.…”
Section: Discussionmentioning
confidence: 99%
“…While no model of clinical staging in BD has been empirically validated, an International Society for Bipolar Disorders task force review concluded that there is sufficient evidence at this time supporting two stages of established BD, distinguishable based on number of episodes (NoE 11 ) and functioning. 12 The task force also proposed that such a dichotomization is likely to be of heuristic value in the treatment of BD, despite lack of validated boundaries or definitions at this time.…”
Section: Staging Models In Bipolar Disordermentioning
confidence: 99%
“…Most commonly, NoE has been used. [15][16][17][18][19] While a potentially useful and plausible proxy, 1 NoE alone cannot fully capture the complexity of the proposed staging phenomenon, 5,9,11 and in particular does not speak to the notion of disease extension. It has been proposed that analogues of physical disease progression in mental disorders may be functional impairment or disability, and cognitive functioning, 3,6,9,20 while proxies such as medical comorbidities and some psychiatric comorbidities better reflect disease extension.…”
Section: Proxies Of Stage In Established Bdmentioning
confidence: 99%